Astaxanthin as a Potential Myocardial Protection in Cardiac Surgery - Januar, Rilman Ilma; Sembiring, Yan Efrata (Journal of Neonatal Surgery, 2025)
Background: Cardiac surgeries requiring cardiopulmonary bypass (CPB) can lead to myocardial ischemia-reperfusion injury (IRI), a condition driven by oxidative stress and inflammation that adversely affects post-operative outcomes. Traditional myocardial protection strategies, including hypothermia, ischemic conditioning, and cardioplegia, have improved patient prognosis but remain limited in completely preventing IRI-related myocardial damage. Aim: This literature review aims to evaluate the potential of astaxanthin (AX), a potent antioxidant carotenoid, as an adjunct myocardial protection strategy during cardiac surgery involving CPB. Methods: A comprehensive review of current literature was conducted focusing on the pathophysiology of IRI during cardiac surgery, existing myocardial protection techniques, and the pharmacological properties of astaxanthin. Preclinical and clinical studies examining AX’s cardioprotective, anti-inflammatory, and antioxidant effects were analyzed. Results: Astaxanthin exhibits superior antioxidant activity compared to traditional antioxidants, with demonstrated efficacy in reducing oxidative stress, inflammation, and apoptosis in preclinical models. Studies show AX enhances mitochondrial function and reduces myocardial fibrosis and remodeling following IRI. Despite promising findings, most evidence is limited to animal models, and human studies remain scarce. Conclusion: Astaxanthin shows significant promise as a novel agent for myocardial protection during cardiac surgery by mitigating IRI-related damage. However, further clinical research is essential to confirm its safety, efficacy, and optimal dosing in human cardiac surgery settings.